Morphometric and performance of Pangasianodon hypophthalmus (Sauvage, 1983) (♀) × Pangasius nasutus (Bleeker, 1976) (♂) hybrid - Mohamed Yusoff, Siti Fairus (2019)
The present study was carried out to assess the morphometric variation and performance of crossbreed of Pangasianodon hypophthalmus (♀) and Pangasius nasutus (♂), (hybrid PH×PN) and its parental species; female, PH (P. hypophthalmus ♀ × P. hypophthalmus ♂); male, PN (P. nasutus ♀ × P. nasutus ♂). The first objective was employed to evaluate the feasibility (breeding performance, growth, survival) and biochemical composition (proximate, fatty acid, and amino acid profiles) of hybrid PH×PN and its parental species. Breeding, growth and survival performance of hybrid PH×PN based on fertilization, hatching, deformity, total length (TL), body weight (BW) and survival resulted in 73.50±1.34%, 65.43±2.24%, 9.93±1.70%, 32.12±5.56 mm, 107.71±9.91 mg, 62.5±6.50%, respectively, which were higher than in P. nasutus, 58.33±1.37%, 13.80±1.05%, 6.98±0.43%, 30.30±1.70 mm, 129.48±15.88 mg, 15.00±15.19%, respectively. Hybrid PH×PN showed higher protein content (25.09±0.22%) than both parental species (PH; 24.86±0.34%; PN: 23.55±0.24%) and higher lipid content (4.34±0.07%) than P. hypophthalmus (3.48±0.05%). Fatty acid and amino acid profiles varied between species, demonstrating high polyunsaturated fatty acids (PUFA) (26.32±1.66%) and total essential amino acids (EAA) (45.56±0.76%) in hybrid PH×PN than its parental species. The second objective examined the morphological variation of hybrid PH×PN and its parental species. Results revealed a distinct vomerin and palatal teeth of hybrid PH×PN. Ten out of the thirty morphometric characters measured, which include prepelvic length, caudal peduncle length, dorsal fin length, pectoral fin length, adipose fin height, anal fin length, adipose fin length, interorbital length, distant snout to isthmus, and predorsal length are the strongest predictors that contributed meaningfully to the species discrimination. The third objective was carried out to characterize the genetic variation of hybrid PH×PN based on molecular marker using mitochondrial DNA (mtDNA) of Cytochrome Oxidase (I) (COI) gene to infer the maternal lineage of hybrid PH×PN and microsatellite marker applied to elucidate the genetic variation. Finding of COI gene revealed hybrid PH×PN shared the same haplotype (HPH1) as P.hypophthalmus which proved the direction of maternal mating of hybrid PH×PN. Microsatellites marker showed genetic variability of hybrid PH×PN as observed over the loci. The fourth objective evaluated the resistance of hybrid PH×PN and its parental species towards bacteria, Aeromonas hydrophila. Results revealed the 96 h-LD50 value of hybrid PH×PN (×105.16 cfu mL-1) was higher than P. nasutus (×103.51 cfu mL-1) but lower than P. hypophthalmus (×106.67 cfu mL-1). Immunological response of the respiratory burst and lysozyme activities, however, significantly higher in hybrid PH×PN prior to challenge but decreased subsequently at 46 and 96 h post challenged. In conclusion, findings of this study revealed morphometric variation is beneficial in identifying and discriminating hybrid PH×PN from its parental species prior to using molecular markers. Genetic characterization using mitochondrial COI I inferred the maternal lineage of hybrid PH×PN. There is a promising performance of important traits in regard to growth, disease resistance, flesh quality particularly on the protein content than P. nasutus, revealing its potential as species for aquaculture.